粘液囊胞を伴った多発性小唾液腺唾石症の1例 - 近津, 大地; 佐藤, 麻梨香; 池畑, 直樹; 金子, 児太郎; 小川, 隆; 杉崎, リサ (日本口腔外科学会雑誌, 2021)
Sialolithiasis rarely originates in the minor salivary glands, and multiple sialoliths in the minor salivary glands is extremely rare. No report in the literature has described sialoliths with concomitant mucous cysts in the minor salivary glands. We report a rare case of multiple mucous cysts and sialoliths in the minor salivary glands. A 73-year-old man presented with an approximately two-year history of a small nodule that he noticed on the left buccal mucosa. He subsequently developed multiple small nodules on the bilateral buccal mucosa and was referred to our hospital for further evaluation. Examination showed multiple, elastic, hard well-defined nodules on the bilateral buccal mucosa. Magnetic resonance imaging revealed several hyperintense cysts on T2-weighted images. A biopsy of the largest nodule revealed sialolithiasis of the minor salivary gland with mucous cysts. All nodules were extirpated under general anesthesia; we extirpated six mucous cysts and many surrounding minor salivary glands. Based on the histopathological evaluation, we diagnosed the patient with sialolithiasis of the minor salivary glands. Three of the six mucous cysts contained sialoliths. The patient’s postoperative course was uneventful, and no recurrence had been observed after one year.